ANALISIS PERHITUNGAN COST VOLUME PROFIT DALAM PERENCANAAN LABA PADA CV. CAHAYA DIRA DI KOTA SEKAYU - Fipiariny; Harpiansi; Fikriyyah Andini (Equivalent : Journal of Economic, Accounting and Management, 2024)
Abstract : This research discusses how to profit planning at CV. Cahaya DIRA in Sekayu city to applicate the analysis Cost Volume Profit. The purpose of this research is to test the effectiveness of the analysis of the calculation of Cost Volume Profit in Profit Planning at CV. Cahaya DIRA that results can be used as a recommendation for the object. Data collection methods used in this research are interviews and observation. The data used are primary and secondary data obtained from CV. Cahaya DIRA. The data analysis technique is by identify sales and costs, analysis profit target at Cost Volume Profit . The results of the study shows the analysis of Cost Volume Profit can help CV. Cahaya DIRA to make decisions of fixed cost and variable cost expenditure. To analysis Cost Volume Profit, you can use Contribution Margin, Break Even Point, Margin Of Safety, Degree Of Operating Leverage also analysis of profit plnning. By this analysis we can calculate the total cost, product, and expected profit. The writer suggests that company management should to increase sales and use analysis Cost Volume Profit to estimate the costs to that have been incurred, the products that have been sold, and the expected profit for one period.  Abstrak : Penelitian ini membahas bagaimana perencanaan laba pada CV. Cahaya DIRA di kota Sekayu dengan menerapkan analisis Cost Volume Profit. Tujuan dari penelitian ini adalah untuk menguji keefektifan analisis perhitungan Cost Volume Profit dalam Perencanaan Laba Pada CV. Cahaya DIRA yang hasilnya dapat digunakan sebagai rekomendasi bagi objek yang diteliti Metode pengumpulan data yang digunakan dalam penelitian ini adalah wawancara dan observasi. Data yang digunakan adalah data primer dan sekunder yang diperoleh dari CV. Cahaya DIRA. Adapun Teknik analisis data dengan cara identifikasi penjualan dan biaya, analisis target laba, analisis Cost Volume Profit. Hasil penelitian menunjukan analisis Cost Volume Profit dapat membantu CV. Cahaya DIRA untuk membuat keputusan pengeluaran biaya tetap dan biaya variabel. Untuk menganalisis Cost Volume Profit dapat menggunakan analisa Contribution Margin, Break Even Point, Margin Of Safety, Degree Of Operating Leverage. serta analisa perencanaan laba. Dengan analisa tersebut kita dapat menghitung jumlah biaya, produk, dan laba yang dicapai. Penulis menyarankan agar manajemen perusahaan harus lebih meningkatkan penjualan dan menggunakan analisa Cost Volume Profit untuk memperkirakan biaya yang akan dikeluarkan, produk yang akan dijual, dan laba yang diharapkan selama satu periode.